DEMAND SIDE AND SUPPLY SIDE ANALYSIS OF INTERNATIONAL SCALE TOURISM ACTIVITIES POST SAIL KOMODO IN EAST NUSA TENGGARA - Agustina Sadri Yathy Lay; Thomas Ola Langoday (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The results of the study show that the six independent variables, namely: Entry Variable (ENT), Long-Distance Transportation (TJJ), Tourism Promotion (PW), Short-Distance Transportation (TJD), Hospitality (HOS) and Supporting Infrastructure (IP) together contribute an influence of 60.30 % on the decision of foreign tourists to visit the Province of East Nusa Tenggara. There are three variables that have a positive and significant influence on the choice of tourists to NTT, namely the ENT variable, TJJ and the PW variable; while the other three variables have no significant influence, namely, TJD , HOS and IP . For domestic tourists, Simultaneously, the five independent variables contribute 87.3% of the influence on the decision of domestic tourists to visit the Province of East Nusa Tenggara. However, partially, TJJ and PW have a significant effect, while TJD , HOS and IP have no significant effect on the choice of domestic tourists to visit the Province of East Nusa Tenggara. industry business before the preparation and implementation of Sail Komodo, shows that both additional investment, additional workforce , tourist visits, additional length of stay and income/turnover of business actors are in the low category. The condition of tourism business actors during the preparation, during and after the implementation of Sail Komodo shows a rapid increase. The three main variables that experienced a rapid increase during the preparation, during the implementation and after the implementation of Sail Komodo are additional tourist visits , additional turnover/ income and additional tourist stay time. Before the implementation of Sail Komodo, the environmental security conditions at tourist locations in NTT were already in the moderate category , compared to other variables that were in the low category . The condition of tourist locations during preparation, during implementation and after the implementation of Sail Komodo were in the moderate category except for additional electricity supply which was in the low category.